2022
DOI: 10.32604/biocell.2022.017609
|View full text |Cite
|
Sign up to set email alerts
|

A mini-review on pharmacological effects of ginsenoside Rb3, a marked saponin from Panax genus

Abstract: Ginsenoside Rb3 (G-Rb3) is one of the primary active compounds isolated from Panax ginseng Meyer, which belongs to protopanaxadiol ginsenosides (PPD). Based on the structure-activity relationship (SAR) of ginsenosides, the pentose structure of G-Rb3 limited itself to possess more pharmacological activity to a certain extent. However, pharmacokinetics show that G-Rb3 is processed through deglycosylation in the intestinal tract and converted into more active rare saponins, such as Compound K, F2, etc. A series o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Nano-selenium biofortification acts the accumulation of Panax notoginseng saponins (Rb3, Rc, F2, Rb2, and Rf). According to various research, these saponins have the potential to alleviate cardiovascular and cerebrovascular disorders induced by HFD ( 28 30 ). Studies showed that selenium deficiency induces Keshan disease, which is characterized by cardiac hypertrophy and increased heart weight ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nano-selenium biofortification acts the accumulation of Panax notoginseng saponins (Rb3, Rc, F2, Rb2, and Rf). According to various research, these saponins have the potential to alleviate cardiovascular and cerebrovascular disorders induced by HFD ( 28 30 ). Studies showed that selenium deficiency induces Keshan disease, which is characterized by cardiac hypertrophy and increased heart weight ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-diabetic, anticonvulsant, antitumor, cardioprotective, antidepressant [22] *B> [12,21] Rc Antiallergic [23], antioxidant [24], anti-inflammatory [25], SIRT1 activation [26] *B> [12] *B< [17] 1.51 ± 0.11 vs. 7.03 ± 2.15 [17]…”
Section: Rb3mentioning
confidence: 99%
“…Given the berry's high concentration of Rb3, Re, Rb2, and Rd, the ginsenosides with demonstrated antidepressant and neuroprotective effects [20,22,27,30,31], it could be expected that the berry has even a superior potential for mental health applications than the root. Still, root extracts and specific ginsenosides have been the subject of most research and have consistently demonstrated efficacy in vitro and in vivo models in the context of central nervous system diseases and depression [53,54].…”
Section: Rg3mentioning
confidence: 99%
“…Previous research has found that versatile primary and secondary metabolites, including saponins, polysaccharides, flavonoids, amino acids, organic acids, and sterols, etc., are present in these plants. Among these, saponins are the primary bioactive components, exhibiting pharmacological effects on the central nervous system, cardiovascular system, and immune system [1,2]. With the development of modern detection technology, active ingredients similar to those in the respective rhizomes and roots have been found in their flower parts [3,4].…”
Section: Introductionmentioning
confidence: 99%